2021
DOI: 10.1051/e3sconf/202127201023
|View full text |Cite
|
Sign up to set email alerts
|

Study of water quality analysis and evaluation of Hengshui Lake

Abstract: The water quality of Hengshui Lake in different regions and at different times was analyzed. According to the data analysis results of chemical oxygen demand (COD), biochemical oxygen demand (BOD5), ammonia nitrogen (NH3-N), total nitrogen (TN), total organic carbon (TOC), total phosphorus (TP), calcium ion content, total hardness, chloride ion content, pH value and conductivity of Hengshui Lake water samples, the water quality of Hengshui Lake was evaluated and analyzed. The results showed that the pollution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
0
2
Order By: Relevance
“…The concentration of TOC exceeded the allowable threshold of QCVN 08-MT:2015/BTNMT column B1 (4 mg/L) by 1.01-4.13 times. TOC in the current study area was found to be higher than that in the study former [25].…”
Section: Physical Parameterscontrasting
confidence: 79%
See 1 more Smart Citation
“…The concentration of TOC exceeded the allowable threshold of QCVN 08-MT:2015/BTNMT column B1 (4 mg/L) by 1.01-4.13 times. TOC in the current study area was found to be higher than that in the study former [25].…”
Section: Physical Parameterscontrasting
confidence: 79%
“…According to [27], the concentrations of nutrients in water depend a lot on the source directly discharged into the water source, when the nutrient concentration in the water is too high, it could affect the biological balance of the water and pollute the water source. Compared with the study of [25], the concentration of TN and TP in the current study area were much higher. The results revealed that surface water quality in Soc Trang province had a high level of nutrients that easily causes eutrophication.…”
Section: Nutritional Parameterscontrasting
confidence: 74%